Digitalization of Fresh Fish Sales: A Study of the E Commerce Model at Toko Ikan Jayapura - Sitti Khairul Bariyyah; Yudi Prayitno; Annita Sari (STIE Amkop Makassar, 2025)
Toko Ikan Jayapura is a fisheries business unit specializing in the sale of fresh fish and local seafood products in Papua. With the increasing demand for digital access and ease of online transactions, this study aims to describe the implementation and effectiveness of a web-based sales model (e-commerce) at Toko Ikan Jayapura. The study was conducted qualitatively from April to June 2025 through interviews, observations, and digital documentation. The results indicate that e-commerce has a significant impact on increasing sales volume, enhancing consumer accessibility, and improving operational efficiency. The developed website enables customers to place orders directly, view product catalogs, make payments, and track deliveries. This model serves as a pilot example of digitalization in the fisheries business in eastern Indonesia.